Yield stress of cemented paste backfill in sub-zero environments: Experimental results. (June 2016) - Haiqiang, Jiang; Fall, Mamadou; Cui, Liang
Highlights: Effect of sub-zero environmental temperatures on the yield stress of cemented paste backfill (CPB) is investigated. The CPB samples exposed to sub-zero temperatures show lower yield stress values than those at room temperature. CPB mix components have significant influence on its yield stress. The findings have significant implications for backfill practices in permafrost and cold regions. Abstract: Current technical knowledge on the rheological behaviour of cemented paste backfill (CPB) is available for mines that have temperatures above zero, but this information is often unreliable when transposed to mines in permafrost or cold regions. The assessment and understanding of the yield stress of CPB and its evolution with time when exposed to sub-zero environmental temperatures are critical for applying CPB technology to underground mines in cold and permafrost regions. Therefore, the aim of this study is to investigate and develop a better understanding of the combined effects of time and sub-zero temperatures on a key rheological property (yield stress) of CPB. Several CPB mixtures of various compositions are exposed to various sub-zero-temperatures (−1 °C, −6 °C and −12 °C) or placed in room temperature up to 4 h. The yield stress of the CPB is determined after specific times. Furthermore, microstructural analyses and electrical conductivity monitoring are conducted on the CPB samples. It is found that the yield stress for the CPB samples exposed to the studied sub-zero temperatures is much lower than that of the sample placed in room temperature. Increases in the water cement ratio and sodium chloride concentration, and decreases in the sub-zero curing temperatures lead to lower yield stress. The results also show that the yield stress of CPB is strongly affected by the mineralogical and chemical compositions of the tailings. The findings of this study have significant implications for backfill practices in permafrost and cold regions.